Complications, Risk Factors, and Staffing Patterns for Noncardiac Surgery in Patients with Left Ventricular Assist Devices. (March 2017) - Mathis, Michael R.; Sathishkumar, Subramanian; Kheterpal, Sachin; Caldwell, Matthew D.; Pagani, Francis D.; Jewell, Elizabeth S.; Engoren, Milo C.
Abstract : Background: Patients with left ventricular assist devices presenting for noncardiac surgery are increasingly commonplace; however, little is known about their outcomes. Accordingly, the authors sought to determine the frequency of complications, risk factors, and staffing patterns. Methods: The authors performed a retrospective study at their academic tertiary care center, investigating all adult left ventricular assist device patients undergoing noncardiac surgery from 2006 to 2015. The authors described perioperative profiles of noncardiac surgery cases, including patient, left ventricular assist device, surgical case, and anesthetic characteristics, as well as staffing by cardiac/noncardiac anesthesiologists. Through univariate and multivariable analyses, the authors studied acute kidney injury as a primary outcome; secondary outcomes included elevated serum lactate dehydrogenase suggestive of left ventricular assist device thrombosis, intraoperative bleeding complication, and intraoperative hypotension. The authors additionally studied major perioperative complications and mortality. Results: Two hundred and forty-six patients underwent 702 procedures. Of 607 index cases, 110 (18%) experienced postoperative acute kidney injury, and 16 (2.6%) had elevated lactate dehydrogenase. Of cases with complete blood pressure data, 176 (27%) experienced intraoperative hypotension. Bleeding complications occurred in 45 cases (6.4%). Thirteen (5.3%) patients died within 30 days of surgery. Independent risk factors associated with acute kidney injury included major surgical procedures (adjusted odds ratio, 4.4; 95% CI, 1.1 to 17.3; P = 0.03) and cases prompting invasive arterial line monitoring (adjusted odds ratio, 3.6; 95% CI, 1.3 to 10.3; P = 0.02) or preoperative fresh frozen plasma transfusion (adjusted odds ratio, 1.7; 95% CI, 1.1 to 2.8; P = 0.02). Conclusions: Intraoperative hypotension and acute kidney injury were the most common complications in left ventricular assist device patients presenting for noncardiac surgery; perioperative management remains a challenge. Abstract : This study characterized complications, risk factors, and staffing patterns for 246 patients with left ventricular assist devices undergoing 702 noncardiac surgical procedures. Intraoperative hypotension and acute kidney injury were the most common complications.Supplemental Digital Content is available in the text.